Manganese Copper Ferrite Thin Films for Visible–Near‐Infrared Region Photodetector Applications. Issue 7 (1st June 2022) - Lee, Yuan-Mau; Lu, You-Yan; Fu, Ching-Tai; Kuo, Chia-Tung; Hou, Lu-Cheng; Chuang, Yu-Hsuan; Chung, Pin-Hung; Wang, Tzu-Hsuan; Liu, Chao-I; Yew, Tri-Rung
Abstract : Herein, p + ‐silicon/air‐annealed manganese copper ferrite (MCF oxide) thin film/indium tin oxide (ITO) stacking photodetectors, capable of detecting light illuminations ranging from the visible to near‐infrared region, are fabricated. The MCF oxide photodetectors composed of earth‐abundant and eco‐friendly metal oxides are fabricated by radio‐frequency (RF) magnetron sputtering. The optical and photoconductive characteristics are investigated by photoluminescence (PL) spectrum, ultraviolet–visible spectroscopy (UV–vis), X‐ray diffractometer (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Defect levels within the wide bandgap of MCF oxide semiconductor enable high sensitivity ranging from visible to near‐infrared illuminations. The device exhibits a fast photoresponse less than 10 ms, a high photosensitivity of 163, and a responsivity of 1.26 A W −1 under a bias voltage of −2 V. The device not only demonstrates peak performances under 800 nm illumination, but also exhibits considerable photosensitivity under visible light illuminations of 630, 532, and 450 nm. The noticeable performances make air‐annealed MCF oxide thin film device a viable candidate for next‐generation photodetectors. Abstract : Attributed to oxygen defects induced intraband levels, the photodetectors using air‐annealed manganese copper ferrite (MCF oxide) thin films exhibit considerable responsivities under near‐infrared to visible light illumination. Moreover, the indium tin oxide (ITO)/air‐annealed MCF oxide/p + ‐Si devices perform rapid photoresponse with a rising time of 6.35 ms and a falling time of 7.26 ms under 800 nm illumination.